Examining the presence and nature of delusions in Alzheimer's disease and frontotemporal dementia syndromes. (17th February 2022) - Kumfor, Fiona; Liang, Cheng Tao; Hazelton, Jessica L.; Leyton, Cristian E.; Kaizik, Cassandra; Devenney, Emma; Connaughton, Emily; Langdon, Robyn; Mioshi, Eneida; Kwok, John B.; Dobson‐Stone, Carol; Halliday, Glenda M.; et al.
Abstract: Objectives: Abnormal beliefs and delusions have been reported in some people with dementia, however, the prevalence of delusions, and their neurocognitive basis has been underexplored. This study aimed to examine the presence, severity, content and neural correlates of delusions in a large, well‐characterised cohort of dementia patients using a transdiagnostic, cross‐sectional approach. Methods: Four‐hundred and eighty‐seven people with dementia were recruited: 102 Alzheimer's disease, 136 behavioural‐variant frontotemporal dementia, 154 primary progressive aphasia, 29 motor neurone disease, 46 corticobasal syndrome, 20 progressive supranuclear palsy. All patients underwent neuropsychological assessment and brain magnetic resonance imaging, and the Neuropsychiatric Inventory was conducted with an informant, by an experienced clinician. Results: In our cohort, 48/487 patients (10.8%) had delusions. A diagnosis of behavioural‐variant frontotemporal dementia (18.4%) and Alzheimer's disease (11.8%) were associated with increased risk of delusions. A positive gene mutation was observed in 11/27 people with delusions. Individuals with frequent delusions performed worse on the Addenbrooke's Cognitive Examination ( p  = 0.035), particularly on the orientation/attention ( p  = 0.022) and memory ( p  = 0.013) subtests. Voxel‐based morphometry analyses found that increased delusional psychopathology was associated with reduced integrity of the right middle frontal gyrus, right planum temporale and left anterior temporal pole. Conclusion: Our results demonstrate that delusions are relatively common in dementia and uncover a unique cognitive and neural profile associated with the manifestation of delusions. Clinically, delusions may lead to delayed or misdiagnosis. Our results shed light on how to identify individuals at risk of neuropsychiatric features of dementia, a crucial first step to enable targeted symptom management. Key points: Delusions showed high prevalence, occurring in 10% of all dementia syndromes. Behavioural‐variant frontotemporal dementia had an increased risk of delusions. Most patients experience polythematic delusions, often and of ranging severity, with delusions being related to more severe attention, orientation and memory deficits. Delusions were more common in people with strong family history/genetic mutations.